PEMBERIAN EDUKASI KEPADA IBU DALAM UPAYA PENCEGAHAN STUNTING PADA BALITA: Giving Education To Mothers In The Effort To Prevent Stunting In Toddlers - Hanik Khairun Nisa (Pakis Journal Institute, 2023)
A child's growth and development may be stunted, which is what we mean when we speak about the concept of stunting. Stunting can be caused by a number of factors, including malnutrition, recurrent illnesses, and/or a lack of psychosocial stimulation. Stunting is a significant problem for the general health of the population in countries of low and moderate income, which have high rates of malnutrition. There is a correlation between growth retardation and both physical and mental health problems, including an increased likelihood of being ill, worse cognitive function, and decreased levels of productivity in adulthood. Expanded opportunities for early childhood education and stimulation, improved access to nutrient-dense foods, increased availability of adequate health care, and promotion of suitable hygiene and sanitation practises are all essential components of an all-encompassing plan to combat stunting. Because of this, the parents of young children in the village of Melati Jaya, which is located in the Rt 001 Rw 001 Semendawai Timur District of the East Oku Regency, are getting counselling that is targeted at avoiding stunting. In order to carry out this action, education was made available in the form of counselling, and media was made available in the form of flyers. The educational events were effective, attracting favourable comments and engagement from the audience members who were the intended recipients of the content. It is clear from a comparison of the results of the pre-test and the post-test that the education provided was successful in raising the respondents' awareness of stunting.